Trichoderma na promoção de crescimento da cultura da soja (Glycine max L.) em diferentes condições edafoclimáticas - Sá, Raquel Andrade (2020)
Among the microorganisms acting on growth promotion, the fungus of the genus Trichoderma is among the main ones, positively influencing seed germination, crop development and yield, having great economic importance for agriculture. In order to evaluate under different edaphoclimatic conditions the potential of two Trichoderma species as growth promoter in soybean (Glycine max L.), four studies were carried out in the cities of Ponta Grossa-PR, Céu Azul-PR. , Dourados-MS and Primavera do Leste-MT, in the 2018/2019 harvest. The statistical design used was randomized blocks, with ten treatments and four replications, using the cultivars TMG 7062 IPRO. The treatments used consisted of: absolute control (absence of product, ie without inoculation of biological product), positive control (commercial product based on three Trichoderma:T. harzianum, T. asperellum and T. koningiopsis) and two species. Trichoderma, T. endophyticum and T. koningiopsis, both at a concentration of 1 x 109UFC/g, with four doses: 50; 100; 150 and 200 g ha-1. The treatments were applied via seed treatment and in two foliar applications, at stage V6 and R1, Fehr & Caviness (1977). A syrup volume of 500 mL 100 kg-1 was applied to the soybean seeds, and the foliar treatments were used a syrup volume of 200 L ha-1. Under the conditions in which the study was developed, it can be concluded that the T treatments endophyticum at 100 g ha-1 and T. koningiopsis at 150 g ha-1 applied to soybean culture via seed and leaf inoculation were able to promote an increase in crop.